Síntese e caracterizações da espuma rígida de poliuretano derivada de óleos vegetais dopada com hidróxido de alumínio - Silva, Ênio Henrique Pires da (2020)
This work presents an experimental approach about the characterization of the main properties of the rigid polyurethane foam derived from renewable sources and doped with aluminum hydroxide as flame retardant. Several standards were used in order to standardize the tests and allow the comparison among the results available in the literature. The materials were prepared in laboratory and the sample densities were the same for all performed tests 180 kg/m³. The main property studied in this work was the foam decreasing flammability as the amount of aluminum hydroxide increased, therefore the standards ASTM D3801 and ASTM D635 were used to evaluate these properties. In order to obtain the foam mechanical properties, the flexural, tensile e compression tests were done following the ASTM D790 for the flexural test and ASTM D1621 for the compression one, moreover, the tensile test was inspired by ASTM D1623, but modified according to some studies in the literature. In addition, tests for acoustic transmission loss (ASTM E2611) and water absorption (ASTM D570) were made. The study on the morphology and homogenization of the material occurred by scanning electron microscopy and dispersive energy spectroscopy, respectively. The flammability tests showed that samples highly doped with flame-retardant 40% and 50% presented satisfactory values that could classify them as V-0 and HB for the vertical and horizontal tests respectively. The Flexural test showed that the maximum stresses were presented by the samples with 20% (1.91 MPa) and 30% (1.85 MPa) of flame retardant. The pure foam maximum stress was 1.55 MPa while foams with 40% and 50% of flame retardant showed values of 1.65 MPa and 1.53 MPa respectively. This variation was disregarded as significant due to the deviations presented by the samples. The ultimate strain decreased as higher the amount of aluminum hydroxide was. The pure foam tensile test presented a maximum stress of 1.29 MPa and this value decreased when the best flammability responsive materials 40% (1.09 MPa) and 50% (1.04 MPa) were tested. The stiffness of the samples with flame retardant had a smooth increase, however, the tensile test in the foams showed a relatively high standard deviation and the difference in stiffness ended up being even less evident. The compression tests showed a significant increase in mechanical strength for the doped foams, increasing the resistance in three times and the stiffness in nine for the 50% aluminum hydroxide doped foam. The sound transmission loss through the foam was not impaired by the addition of aluminum hydroxide, on the contrary, these values reached higher numbers in some materials. Foam morphology and the flame-retardant distribution within the foam were observed as random. Therefore, this work provides important information that can increase the range of applications of rigid polyurethane foam derived from vegetable oils, such increment is important due to the environmental appeal that surrounds society nowadays.